Le dilemme des assureurs face aux tribunaux : régler ou contester ? - Levesque, Louise (Assurances)

(untitled) (HEC Montréal, 1991)
Should a claim be paid or contested? Every day, insurers and their employees, adjusters, lawyers are confronted with this dilemma. Economical, judicial and strategic considerations underlying the insurers' decisions will be reviewed. The courts' alternative for settlement of claims will also be looked into.